IMPLEMENTATION OF STRATEGIC MANAGEMENT IN IMPROVING THE PERFORMANCE OF PUBLIC SECTOR ORGANIZATIONS - HARKIM; REJEKIA VAIZAL SIMANUNGKALIT (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The strategic management model, apart from being applied to the private sector, is also applied to the public sector. The implementation of strategic management in the two sectors is actually not that much different, it's just that public sector institutions do not emphasize organizational goals for profit, but rather on service to the community. The strategy management stage begins with strategy formulation, strategy implementation and strategy evaluation. The implementation of strategic management in the public sector is one of the best ways to achieve good governance. In an effort to achieve a better performance of government organizations in providing services to the community, the implementation of strategic management for public sector organizations is very important to increase the effectiveness of the performance of public sector organizations. This requires public sector organizations to think strategically, be able to translate their inputs into effective strategies, and develop the reasons needed to lay the foundation for implementing their strategies. It is hoped that the implementation of strategic management in public sector organizations can help these organizations realize their vision and mission. Although the results orientation to be achieved with the implementation of strategic management between the private sector and the public sector is slightly different, the two sectors certainly face different environmental conditions which become separate obstacles in the process of implementing strategic management. To overcome the obstacles that occur, one of them is by using a SWOT analysis approach (strength, weakness, opportunity, and threats). In this paper, we will discuss conceptually the theoretical aspects of implementing strategic management in measuring the performance of public sector organizations, and will also discuss the constraints that occur in measuring the performance of public sector organizations.